2009
DOI: 10.1113/jphysiol.2008.159616
|View full text |Cite
|
Sign up to set email alerts
|

An energy supply network of nutrient absorption coordinated by calcium and T1R taste receptors in rat small intestine

Abstract: T1R taste receptors are present throughout the gastrointestinal tract. Glucose absorption comprises active absorption via SGLT1 and facilitated absorption via GLUT2 in the apical membrane. Trafficking of apical GLUT2 is rapidly up-regulated by glucose and artificial sweeteners, which act through T1R2 + T1R3/α-gustducin to activate PLC β2 and PKC βII. We therefore investigated whether non-sugar nutrients are regulated by taste receptors using perfused rat jejunum in vivo. Under different conditions, we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 68 publications
(128 reference statements)
5
114
1
Order By: Relevance
“…In the pancreas, sweet taste receptor activation has been reported to potentiate glucose-stimulated insulin secretion (34,49). In the intestine, this receptor has been implicated in glucose absorption, whereas ␣-gustducin has been shown to be critical for glucose-stimulated incretin secretion (31,(41)(42)(43) from enteroendocrine cells. Mice lacking ␣-gustducin exhibit decreased expression of the Na ϩ -glucose cotransporter SGLT1 in the intestine, elevated blood glucose levels, a delayed rise in plasma insulin levels, and a diminished incretin response after a glucose challenge compared with controls (31,43).…”
mentioning
confidence: 99%
“…In the pancreas, sweet taste receptor activation has been reported to potentiate glucose-stimulated insulin secretion (34,49). In the intestine, this receptor has been implicated in glucose absorption, whereas ␣-gustducin has been shown to be critical for glucose-stimulated incretin secretion (31,(41)(42)(43) from enteroendocrine cells. Mice lacking ␣-gustducin exhibit decreased expression of the Na ϩ -glucose cotransporter SGLT1 in the intestine, elevated blood glucose levels, a delayed rise in plasma insulin levels, and a diminished incretin response after a glucose challenge compared with controls (31,43).…”
mentioning
confidence: 99%
“…[158][159][160][161][162][163] In contrast, stress, a high-fat diet, and glucocorticoids inhibit GLUT2 trafficking to the brush border membrane. [164][165][166] Most recently, subcellular localization studies using live cell imaging demonstrated that GLUT2 is endocytosed through a caveolae-dependent mechanism, which is partially recovered in Rab11A-positive recycling endosomes.…”
Section: Glut2 and Glut3mentioning
confidence: 99%
“…Supplementation of the diet with sucralose increases the expression of SGLT1 in the enterocytes of wild-type mice, but not in mice deficient in T1R3 or a-gustducin (4) . The presence of sucralose enhances insertion of GLUT2 into the apical region of the enterocytes, and thus, stimulates glucose absorption in rats (7,8) . For example, sucralose administration doubled the level of GLUT2 protein…”
mentioning
confidence: 99%